1981
DOI: 10.1111/j.1365-2621.1981.tb04852.x
|View full text |Cite
|
Sign up to set email alerts
|

Selected Quality Factors and Sensory Attributes of Cured Ham as Influenced by Different Phosphate Blends

Abstract: In each of four replications, 32 packer-style hams were randomly allotted to one of eight treatment groups in which the curing brine formulated for a 10% pump contained: (1) No phosphate; (2) 100% sodium tripolyphosphate (STP); (3) 5% sodium hexametaphosphate (SHMP) + 95% STP; (4) 10% SHMP + 90% STP; (5) 5% Quadrafos (SQ) + 95% STP; (6) 10% SQ + 90% STP; (7) 10% tetrasodium pyrophosphate (TSPP) + 90% SIP; or (8) 20% TSPP + 80% STP. Raw hams were subjectively evaluated for quality, samples were removed for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…The appearance of cooked meat products can be influenced by pH, meat source, packaging conditions, freezing history, fat content, added ingredients and preservation treatments such as irradiation and pressure (King and Whyte, 2006). Froning (1966) reported that the addition of phosphates tended to darken the meat, while other workers observed that phosphates improve the color of the finished products (Vollmar and Melton, 1981;Wierbicki et al, 1976). But the present study found that the addition of phosphate improved sensory color of cooked patties, but didn't affect on the sensory color of reheated patties.…”
Section: Visual Color and Appearance Propertiescontrasting
confidence: 50%
“…The appearance of cooked meat products can be influenced by pH, meat source, packaging conditions, freezing history, fat content, added ingredients and preservation treatments such as irradiation and pressure (King and Whyte, 2006). Froning (1966) reported that the addition of phosphates tended to darken the meat, while other workers observed that phosphates improve the color of the finished products (Vollmar and Melton, 1981;Wierbicki et al, 1976). But the present study found that the addition of phosphate improved sensory color of cooked patties, but didn't affect on the sensory color of reheated patties.…”
Section: Visual Color and Appearance Propertiescontrasting
confidence: 50%
“…When these phosphates are added, the pH is altered. Alkaline phosphates increase the pH of the meat between 0.1 and 0.6 units, with pyrophosphate increasing it the most, followed by tripolyphosphate and hexametaphosphate [ 40 ]. According to European legislation, phosphates in any of their formulations (E-338-452) have a very limited use in some traditional or prepared meat products (Regulation (CE) No.…”
Section: Innovation and Development In The Use Of Ingredients And Add...mentioning
confidence: 99%
“…In restructured beef steaks, phosphate and salt addition improved texture and had no negative effects on color over time (Lamkey et al, 1986). Hams without phosphate had greater drip and cook losses and received lower palatability scores than hams containing phosphate (Vollmar & Melton, 1981). The function of phosphate to chelate iron has been observed to improve cured color development.…”
Section: Sensory Characteristicsmentioning
confidence: 97%